Produktivitas Aparatur Administratif dalam Perspektif Kapabilitas Kerja Individual pada Pemerintah Daerah Kabupaten Banggai: Administrative Apparatus Productivity from the Perspective of Individual Work Capability in Banggai Regency Government - Clara Neltje Meini Rotinsulu; Feronika Angelina Makahinda (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2026)
This study aimed to analyze administrative apparatus productivity from the perspective of individual work capability at the General Affairs Division of the Banggai Regent Office. The study used a quantitative approach with a saturated sample of 35 employees. Data were collected using a Likert-scale questionnaire and analyzed through simple linear regression, correlation, coefficient of determination, and t-test. The results showed the regression equation Y = 22.798 + 0.173X, a correlation coefficient of 0.245, an R Square of 0.056, and a p-value of 0.178. These findings indicate that individual work capability had a positive but weak and statistically insignificant relationship with apparatus productivity. Individual work capability explained only 5.6% of productivity variation; therefore, administrative apparatus productivity should be understood as an interaction among individual capability, work systems, leadership, motivation, discipline, and technological support. This article emphasizes the need to strengthen public human resource management beyond employee capability development toward improving administrative work governance.